ANALISIS PERILAKU KONSUMEN DALAM BERBELANJA DI PASAR TRADISIONAL - Siti Zuliakha W (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2009)
The aims of this research are (1) to analyze factors that considered by customers to shopping in traditional market, (2) to to analyze the differentiation of factors that considered by customers to shopping in traditional market base on income level, (3) to to analyze cutomer’s opinion regarding consideration to shopping in traditional market or modern market base on comodity.Sampel in this research are 100 responden with criteria have shoped in traditional market and modern market, 15 yers old or more, and shopping by self decision.Factor analysis and qualitative descriptive analysis used to examine the hypotheses.. The results of this research shown that (1) There are 8 factors that considered by customers to shopping in traditional market, (2) There is no differentiation of factors that considered by customers to shopping in traditional market base on income level, (3) there is no differentiation of factors considered by customers to shopping in traditional market or modern market base on comodity.